Metodologia para utilização de simulação em projetos de manufatura enxuta em engenharia de produção - Clenio Senra de Oliveira (2008)
The search for the competitiveness in the market has forced the manufacturing enterprises to look for new models to production administration, in a way to produce goods with the customers quality desire and low cost. The results of Toyota, one of the major automobile industries around the world at the present time, and its profit andproductivity higher than its competitors, have attracted the attention of enterprises that make reference at the Toyota Production System. Developed after the Second World War, is also known as Lean Manufacturing, and has the main objective to eliminate waste in the production system. But many of the enterprises do not have had success in this strategy implementation, perhaps the effort to copy the Toyota System to their particularly production process is the reason for the unsuccessful initiative. This paper search a base to support organizations to implementing lean manufacturing, focus onprocess simulation, reducing costs of trial and error, common in this kind of project. Do not look for formalizing a methodology, but facilitate the production managers, using the simulation as base to their decision process.